Impact of autograft-absolute lymphocyte count on survival in double/triple hit lymphomas post-autologous stem cell transplantation. Issue 10 (24th August 2022) - Porrata, Luis F.; Inwards, David J.; Ansell, Stephen M.; Micallef, Ivana N.; Johnston, Patrick B.; Villasboas, Jose C.; Paludo, Jonas; Markovic, Svetomir N.
Abstract: The autograft absolute lymphocyte count (A-ALC) ≥0.5 × 10 9 cells/kg is a survival prognostic factor for lymphoma patients undergoing autologous peripheral blood hematopoietic stem cell transplantation (APBHSCT). However, the A-ALC has not be tested as prognostic factor against double hit/triple hit lymphomas (DHL/THL). Thus, we set up to investigate if A-ALC is a prognostic factor for overall survival (OS) and progression-free survival (PFS) for DHL/THL post-APBHSCT. From January 2012 until December 2020, we identified 77 DHL/THL patients treated with APBHSCT. All patients required to have the diagnosis of DHL/THL by FISH for rearrangements of MYC, BCL2, and BCL6. With a median follow-up of 20.4 months (range, 0.4-94.5 months), DHL/THL patients infused with A-ALC ≥0.5 x 10 9 cells/kg experienced superior OS (HR = 0.251, 95%CI 0.117–0.539, p  < 0.0004) and PFS (HR = 0.347, 95%CI 0.160–0.753, p  < 0.007). Multivariate analysis showed that A-ALC was an independent predictor for OS (HR =0.119, 95%CI 0.030–0.473, p  < 0.003) and PFS (HR = 0.400, 95%CI 0.189–0.850, p  < 0.02). Our study showed that A-ALC is a prognostic factor for survival in DHL/THL. Our current practice for lymphoma patients is to collect enough stem cell but also A-ALC to improve clinical outcomes post-APBHSCT.